Loss of Mgat5a-mediated N-glycosylation stimulates regeneration in zebrafish. Issue 1 (December 2016) - Pei, Wuhong; Huang, Sunny; Xu, Lisha; Pettie, Kade; Ceci, María; Sánchez, Mario; Allende, Miguel; Burgess, Shawn
Abstract Background We are using genetics to identify genes specifically involved in hearing regeneration. In a large-scale genetic screening, we identifiedmgat5a, a gene in theN -glycosylation biosynthesis pathway whose activity negatively impacts hair cell regeneration. Methods We used a combination of mutant analysis in zebrafish and a hair cell regeneration assay to phenotype the loss of Mgat5a activity in zebrafish. We used pharmacological inhibition ofN -glycosylation by swansonine. We also used over-expression analysis by mRNA injections to demonstrate how changes inN -glycosylation can alter cell signaling. Results We found thatmgat5a was expressed in multiple tissues during zebrafish embryo development, particularly enriched in neural tissues including the brain, retina, and lateral line neuromasts. Anmgat5a insertional mutation and a CRISPR/Cas9-generated truncation mutation both caused an enhancement of hair cell regeneration which could be phenocopied by pharmacological inhibition with swansonine. In addition to hair cell regeneration, inhibition of theN -glycosylation pathway also enhanced the regeneration of lateral line axon and caudal fins. Further analysis showed thatN -glycosylation altered the responsiveness of TGF-beta signaling. Conclusions The findings from this study provide experimental evidence for the involvement ofN -glycosylation in tissue regeneration and cell signaling.